Synthesis, magnetoresistance, and thermoelectrical properties of environmentally stable n-type nitrogen-doped multiwalled carbon nanotubes - Andzane, Jans; Katkov, Mikhail V.; Buks, Krisjanis; Sarakovskis, Anatolijs; Smits, Krisjanis; Erts, Donats (Elsevier, 2023)
Nitrogen-doped multiwalled carbon nanotubes (N-MWCNTs) are known as a perspective material for a variety of applications in nanoelectronic devices, sensors, catalysts for carbon dioxide reduction, and flexible thermoelectrics. However, up to date most of the reports on the properties of N-MWCNTs are focused on a narrow niche of research, for example, a study of low-temperature magnetoresistance or room-temperature thermoelectrical properties. In this work, N-MWCNTs were synthesized using benzene:pyridine precursor in different ratios, and both magnetoresistance and thermoelectrical properties of the synthesized N-MWCNTs were systematically investigated in the temperature range 2-300 K and compared with the properties of undoped MWCNTs. Unexpected switching of the magnetoresistance of the N-MWCNTs at low temperatures from negative to positive values was observed, and the processes underlying this effect are discussed. The study of the thermoelectrical properties revealed n-type conductance in the N-MWCNTs, which was attributed to the impact of nitrogen defects incorporated in the MWCNT structure. Performed for the first-time investigations of the thermal stability of the Seebeck coefficient of N-MWCNTs in air revealed that the Seebeck coefficient retains its negative values and even increases after annealing of the N-MWCNTs in air at 500 °C. These findings illustrate the high potential of the presented in this work N-MWCNTs for applications in different devices in a wide range of temperatures. --//-- Jana Andzane, Mikhail V. Katkov, Krisjanis Buks, Anatolijs Sarakovskis, Krisjanis Smits, Donats Erts, Synthesis, magnetoresistance, and thermoelectrical properties of environmentally stable n-type nitrogen-doped multiwalled carbon nanotubes, Carbon Trends, Volume 13, 2023,100302, ISSN 2667-0569, https://doi.org/10.1016/j.cartre.2023.100302. (https://www.sciencedirect.com/science/article/pii/S2667056923000573). Published under the CC BY-NC-ND licence.
This work was funded by the European Regional Development Fund (ERDF) project no. 1.1.1.1/19/A/138. A.S. and K. S. acknowledge the funding from the European Union's Horizon 2020 Framework Programme H2020-WIDESPREAD-01-2016-2017-Teaming Phase2 under grant agreement No. 739508, project CAMART2.
Keywords: nitrogen-doped multiwalled carbon nanotubes; N-MWCNT; pyridine; Seebeck coefficient; annealing stability; low-temperature magnetoresistance